Malaysian SMEs m-commerce adoption : TAM 3, UTAUT 2 and TOE approach - Salimon, Maruf Gbadebo; Kareem, Olanrewaju; Sany Sanuri, Mohd Mokhtar; Abdullateef, Aliyu Olayemi; Bamgbade, Jibril Adewale; Adeleke, Adekunle Qudus (Emerald Publishing, 2023)
The purpose of this study is to examine the factors that influence Malaysian Small and Medium Enterprises (SMEs) to adopt mobile commerce (m-commerce) by integrating the constructs of Technology Acceptance Model 3 (TAM 3), Universal Theory of Acceptance and Use of Technology 2 and Technology-Organization-Environment model. Though numerous m-commerce adoption (MCA) studies have been conducted, lesser attention is paid to how hedonic motivation (HM) can influence organizational users such as SMEs. This study bridges the gap by integrating the three models to provide a new lens to guide SMEs. Design/methodology/approach: To examine the factors that influence the adoption of m-commerce, the researchers collected data from SMEs in Malaysia using an online survey. The sample size of the participants was determined through the available list provided by SME Corp Malaysia. The researchers also used Krejcie and Morgan’s sample size and G * Power techniques to determine that the sample size was appropriate. The data collected were analyzed using partial least square-structural equation modeling. Findings: The findings of this study reveal that technological factors (computer self-efficacy [CSE], result demonstrability [RD] and computer anxiety [CA]) positively and significantly influence MCA. Likewise, the organizational/environmental factors (m-commerce knowledge, pressure from trading partners and pressure from competitors) positively and significantly influence MCA. The moderating influence of HM was also achieved on the relationship between CSE and RD. However, the proposed hedonic moderating relationship between CA and the adoption of m-commerce is not significant. Research limitations/implications: This study integrates three models to explain the adoption of m-commerce among SMEs in Malaysia and tested the moderating influence of HM. The results obtained better explain the decision by the SMEs to use m-commerce. Originality/value: The study critically considered how m-commerce can be adopted by SMEs in Malaysia, which previous studies have largely ignored. Considering this, the study, therefore, advances a new relationship by integrating Technology-organization-environment model with TAM 3 and the moderating influence of HM to explain MCA among SMEs. This paper is one of the few research studies to test the moderating influence of HM in this regard.